Dicer regulates Nosema ceranae proliferation in honeybees. Issue 1 (24th October 2018) - Huang, Q.; Li, W.; Chen, Y.; Retschnig‐Tanner, G.; Yanez, O.; Neumann, P.; Evans, J. D.
Abstract: Nosema ceranae is a microsporidian parasite that infects the honeybee midgut epithelium. The protein‐coding gene Dicer is lost in most microsporidian genomes but is present in N. ceranae . By feeding infected honeybees with small interfering RNA targeting the N. ceranae gene coding Dicer (siRNA‐Dicer), we found that N. ceranae spore loads were significantly reduced. In addition, over 10% of total parasite protein‐coding genes showed significantly divergent expression profiles after siRNA‐Dicer treatment. Parasite genes for cell proliferation, ABC transporters and hexokinase were downregulated at 3 days postinfection, a key point in the middle of parasite replication cycles. In addition, genes involved in metabolic pathways of honeybees and N. ceranae showed significant co‐expression. Furthermore, the siRNA‐Dicer treatment partly reversed the expression patterns of honeybee genes. The honeybee gene mucin‐2‐like showed significantly upregulation in the siRNA‐Dicer group compared with the infection group continually at 4, 5 and 6 days postinfection, suggesting that the siRNA‐Dicer feeding promoted the strength of the mucus barrier resulted from interrupted parasite proliferation. As the gene Dicer broadly regulates N. ceranae proliferation and honeybee metabolism, our data suggest the RNA interference pathway is an important infection strategy for N. ceranae .